2016
DOI: 10.5511/plantbiotechnology.16.0627a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cuticle accumulation by employing MIXTA-like transcription factors

Abstract: The cuticle covers almost the entire aerial surface of terrestrial plants, and provides protection from abiotic and biotic stresses. Cuticles basically consist of wax and cutin, and are produced with variable structures and thicknesses depending on the plant and organ. The application of plant cuticles to improve stress tolerance and wax production requires the deposition of the cuticle at specific times to avoid undesirable side effects. We previously showed that the MYB106 and MYB16 MIXTA-like transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Several transcription factors, such as SVP, MYB48, ERF1 , acting in phytohormone pathways and involved in biotic and abiotic stresses were also upregulated in RNAi‐ ddm1 lines in comparison to WT under water deficit (Sun & Yu, 2015; Bechtold et al ., 2016; He et al ., 2016; Wang et al ., 2017; Heyman et al ., 2018; Wang et al ., 2018; Guo et al ., 2019). Other DEGs, including genes involved in the leaf cuticle and waxes ( MYB106 , CER8 , FLA12 ), could also partly explain the improved tolerance to moderate water deficit in RNAi‐ ddm1 lines by preventing uncontrolled water loss (Chen et al ., 2011; Oshima & Mitsuda, 2013, 2016; Wettstein‐Knowles, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors, such as SVP, MYB48, ERF1 , acting in phytohormone pathways and involved in biotic and abiotic stresses were also upregulated in RNAi‐ ddm1 lines in comparison to WT under water deficit (Sun & Yu, 2015; Bechtold et al ., 2016; He et al ., 2016; Wang et al ., 2017; Heyman et al ., 2018; Wang et al ., 2018; Guo et al ., 2019). Other DEGs, including genes involved in the leaf cuticle and waxes ( MYB106 , CER8 , FLA12 ), could also partly explain the improved tolerance to moderate water deficit in RNAi‐ ddm1 lines by preventing uncontrolled water loss (Chen et al ., 2011; Oshima & Mitsuda, 2013, 2016; Wettstein‐Knowles, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that trichome‐related MYB regulators might be different among plant species. Additionally, AtMYB16 and its closely related MYBs such as AmMYBML2 in Antirrhinum majus and PhMYB1 in Petunia hybrid have similar functions in regulating the development of conical epidermal cells in petals (Baumann et al ., 2007; Di Stilio et al ., 2009; Oshima & Mitsuda, 2016). Here, our results showed that PpMYB25 and PpMYB26 had high levels of expression in petal (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, plants expressing MYB16 driven by the promoter of another downstream target, CYP86A4, do not show any stomatal phenotype. (Oshima and Mitsuda, 2016) Given that stomatal clusters are in CYP77A6p::MYB16-VP16 plants only, we wondered whether CYP77A6 or CYP86A4 has a distinct expression pattern in epidermis. We analyzed their transcriptional reporters by fusing promoters with nucleus-localized fluorescent protein (nucEGFP) and distinguished stomatal linage cells by staining cell outlines with propidium iodide (PI).…”
Section: Stomatal Clusters Have Been Found In Plants Expressing An Ectopic Form Of Myb16mentioning
confidence: 99%
“…The form was created by fusion with the promoter from its downstream target, CYP77A6, and a transcription activation domain, VP16. Of note, plants expressing MYB16 driven by the promoter of another downstream target, CYP86A4, do not show any stomatal phenotype (Oshima and Mitsuda, 2016). Given that stomatal clusters are in CYP77A6p::MYB16-VP16 plants only, we wondered whether CYP77A6 or CYP86A4 has a distinct expression pattern in epidermis.…”
mentioning
confidence: 98%